Paralelismo para a nova era: a evolução da inteligência artificial frente ao engajamento do consumidor na relação de consumo - Silva, Enedino Januário de Miranda e (2021)
This dissertation aims to observe the evolution of the consumption relationship and the development of specific legislation for the protection of consumers across the globe. Legal consumer relations stem from historical concepts of antiquity, developing according to the evolution of society on all continents and landing with great prominence after the Brazilian redemocratization pertinent to the civic movements proper at the time. After 30 years of the enactment of the Consumer Protection Code, a new consumerist paradigm is faced, driven by consumer engagement in the face of the Technological Revolution, building a new consumer relationship with efficient alternatives for conflict resolution and assisting desjudicialization as observed in the research of the Master's Program in Law at the Nove de Julho University - UNINOVE Justice and the Efficiency Paradigm.